(untitled) (Communications in Computational Physics, 2018)
The paper addresses the Large-Eddy Simulation (LES) of the turbulent wake of the Ahmed car model. To this end we use a Fourier-Chebyshev multi-domain solver and the LES capability is implemented through the use of the Spectral Vanishing Viscosity (SVV) method, completed with a near-wall correction. A "pseudo-penalization" technique is used to model the bluff body. Comparisons of the present SVV-LES results with the experiments and also with a more classical Finite Volume LES are provided.